2012
DOI: 10.3390/ijerph9113883
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis Outbreaks in Nicaragua: Identifying Critical Areas and Exploring Drivers for Evidence-Based Planning

Abstract: Leptospirosis is an epidemic-prone zoonotic disease that occurs worldwide. In Central America, leptospirosis outbreaks have been reported in almost all countries; Nicaragua in particular has faced several outbreaks. The objective of this study was to stratify the risk and identify “critical areas” for leptospirosis outbreaks in Nicaragua, and to perform an exploratory analysis of potential “drivers”. This ecological study includes the entire country (153 municipalities). Cases from 2004 to 2010 were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 20 publications
2
46
3
7
Order By: Relevance
“…In addition, these departments together reported 1001 human cases that represented 50.6% of all cases of leptospirosis reported in Nicaragua between 2004 and 2010, time period of the previous study that identified the critical areas using the same database with country official information [4]. Chinandega and Leon have been identified by local experts and in the previous study as risk areas for having the highest incidence rates among all municipalities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these departments together reported 1001 human cases that represented 50.6% of all cases of leptospirosis reported in Nicaragua between 2004 and 2010, time period of the previous study that identified the critical areas using the same database with country official information [4]. Chinandega and Leon have been identified by local experts and in the previous study as risk areas for having the highest incidence rates among all municipalities.…”
Section: Methodsmentioning
confidence: 99%
“…Urbanization and climate change can cause an increase in the frequency and intensity of these factors, consequently increasing the incidence of the disease and the occurrence of outbreaks [3]. Other studies have also found an association between soil types, particularly in relation to its ability to retain moisture, and the levels of proliferation of leptospira [4,7]. Alkaline and neutral soil types, especially of volcano origin, may facilitate longer survival of the bacteria [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Sri Lanka, where CKDu is highly prevalent in the central dry zone with paddy field, leptospirosis outbreaks were found notably in historic record, with the most recent ones in 2008 and 2011 [14,15]. Another example is the sugarcane fields in Chichigalpa, Chinandega in Nicaragua, a focus of CKDu development, where leptospirosis is prevalent, with a major outbreak occurring in 1995 after flooding [16,17]. In these CKDu patients, some have experienced clinical manifestations of acute infection, similar to having episodes of acute leptospirosis [18].…”
Section: Ckd Hotspots Versus Leptospirosis Global Mapmentioning
confidence: 99%
“…In 2007 and 2010, 685 and 653 cases were reported in this country, respectively [17]. After a typhoon in 2009, an outbreak of leptospirosis occurred in the Philippines.…”
Section: Epidemiologymentioning
confidence: 96%